Pelaksanaan Layanan Anak Berkebutuhan Khusus Di SMPN 2 Lamongan Dalam Memenuhi Hak Atas Pendidikan - Putri, Virta Aprilia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the implementation of educational services for children with special needs at SMP Negeri 2 Lamongan as part of an effort to realize equal and fair educational rights. The background of this study is based on the urgency of protecting children’s rights as regulated in Law Number 20 of 2003 concerning the National Education System and Government Regulation Number 13 of 2020 concerning Appropriate Accommodation for Students with Disabilities. Although the policy supports inclusive education, real conditions in schools show challenges, such as the lack of special assistant teachers, limited training for teaching staff, and inadequate facilities. The purpose of this study is to describe the implementation of inclusive education services for children with special needs at SMPN 2 Lamongan and to identify the extent to which their educational rights have been fulfilled based on inclusive principles. The study was conducted using a descriptive qualitative approach, utilizing observation methods, in-depth interviews, and documentation. The findings show that schools have begun implementing inclusive education through curriculum adaptation, as well as collaboration between general teachers and assistant teachers. The learning environment is also directed to be inclusive and respect diversity. However, the implementation of inclusive education has not been fully optimal because there are still technical obstacles and limitations in human resources and facilities and infrastructure. Based on these findings, it can be concluded that although schools have shown seriousness in implementing inclusive education, additional support is still needed so that the educational rights of children with special needs can be realized comprehensively according to the principles formulated by Tomasevski.